Spectrophotometric analysis of post-mortem lividity: A new objective measure to define time of death. (November 2022) - De Donno, Antonio; Calvano, Mariagrazia; Lauretti, Chiara; Angrisani, Carmelinda; Santoiemma, Ilaria; Introna, Francesco
Abstract: The correct definition of time of death often represents a key to solving judicial cases. One of the methods for determination of the time interval since death is at present the quantitative and qualitative characteristics of hypostases. However, the simple observation of the degree and fixation of hypostases is based on nonobjective parameters, and is therefore characterized by an intrinsic variability that can compromise their reliability. The purpose of the present study was to define an objective and standardizable method that allows estimation of time since death with good approximation. To achieve this, the instrument used was based on spectrophotometry, to analyze only the hemoglobin contribution to skin color, while excluding the role of melanin. This made it possible to analyze a hypostatic area, with a numerical value defined as a measure of the hemoglobin content before and after application of standardized pressure for a defined time interval. The study was conducted on 100 cadavers in various wards. The variables considered in the study were: Hb-pre (mean hemoglobin measure before weight force application); Hb-post (mean hemoglobin measure after weight force application), Δ Hb (change in mean hemoglobin measures from before to after weight force application); and red% Hb (percentage reduction in hemoglobin after weight force application, compared to the mean measure of hemoglobin before weight force application). The analysis showed statistically significant correlations between red% Hb in the skin area analyzed and time from death to examination. This provided a mathematical formula to estimate time since death with good reliability ( ± 4 h, 50 min). Highlights: mathematical formula to estimate time since death. standardized procedure to define more precisely time of death. correlation of the time since death with the degree of paleening of the hypostases. Spectrophotometer method to standardize the assessment the intensity of hypostases.